Lamp2a is required for tumor growth and promotes tumor recurrence of hepatocellular carcinoma - Ding, Zhen-Bin; Fu, Xiu-Tao; Shi, Ying-Hong; Zhou, Jian; Peng, Yuan-Fei; Liu, Wei-Ren; Shi, Guo-Ming; Gao, Qiang; Wang, Xiao-Ying; Song, Kang; Jin, Lei; Tian, Meng-Xin; et al. (International journal of oncology, 2016)
Exploring the function of chaperone-mediated autophagy (CMA) in cancer has promoted progress in cancer treatment through the regulation of CMA pathways. However, CMA status and function in hepatocellular carcinoma (HCC) by focusing on the regulatory role of lysosome-associated membrane protein type 2a (Lamp2a) remain to be clarified. We examined Lamp2a in a normal human liver cell line, 6 HCC cell lines, 10 normal liver samples as well as 42 HCC tissue and para-tumor tissues samples, and then validated it in 228 HCC patients to assess the relationship between Lamp2a and clinical prognosis. Gain and loss of Lamp2a function were also explored in HCC cell lines and xenograft models. Significantly lower level of Lamp2a expression was found in HCC cells and tissues compared with normal hepatic cells, para-tumor tissues and normal livers. Although no differences in HCC cell morphology or function were observed in relation to Lamp2a expression under normal culture or short-term starvation conditions, Lamp2a blockage significantly inhibited HCC cell viability under prolonged starvation. Critically, Lamp2a is required for HCC xenograft growth in vivo by helping cells to avoid apoptosis and promoting cell proliferation. Furthermore, a significant correlation between Lamp2a expression and tumor size or cumulative recurrence was uncovered in HCC patients. Collectively, the present study shows that impaired Lamp2a expression in HCC contributes to tumor cell viability and promotes tumor growth and recurrence. Targeting chaperone-mediated autophagy through Lamp2a may also imply a potentially novel treatment strategy for HCC.